Digital Tele-Counseling for Sustainable Maternal Health Services in Indonesia Focus on Telelactation - Dewanti, Lintang Purwara; Sitoayu, Laras; Idarto, Areta (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2024)
Breastfeeding is essential for infant health and development, yet Indonesia faces challenges in meeting global breastfeeding targets. This review examines the potential of tele-counseling (telelactation) as a solution to improve breastfeeding support in the digital era, focusing on overcoming geographical and service delivery barriers. A systematic literature search covering PubMed, Scopus, Google Scholar, and local Indonesian journals identified 25 articles from 2019 to 2023, with 14 unique studies meeting inclusion criteria. Findings indicate that telelactation primarily utilizes WhatsApp groups, Androidbased apps, and online counseling sessions, resulting in improved breastfeeding techniques, increased exclusive breastfeeding rates, and enhanced maternal knowledge. However, privacy concerns and technological barriers persist, though these are addressed through specialized training and ongoing support for healthcare providers. Telecounseling demonstrates promise in supporting breastfeeding in Indonesia, though further research is needed to address geographical limitations and assess longterm impacts. Integrating telecounseling into national breastfeeding policies could significantly advance maternal and child health outcomes in Indonesia.